3(6x-4)-x=2x-6(7-2x)

Simple and best practice solution for 3(6x-4)-x=2x-6(7-2x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(6x-4)-x=2x-6(7-2x) equation:



3(6x-4)-x=2x-6(7-2x)
We move all terms to the left:
3(6x-4)-x-(2x-6(7-2x))=0
We add all the numbers together, and all the variables
3(6x-4)-x-(2x-6(-2x+7))=0
We add all the numbers together, and all the variables
-1x+3(6x-4)-(2x-6(-2x+7))=0
We multiply parentheses
-1x+18x-(2x-6(-2x+7))-12=0
We calculate terms in parentheses: -(2x-6(-2x+7)), so:
2x-6(-2x+7)
We multiply parentheses
2x+12x-42
We add all the numbers together, and all the variables
14x-42
Back to the equation:
-(14x-42)
We add all the numbers together, and all the variables
17x-(14x-42)-12=0
We get rid of parentheses
17x-14x+42-12=0
We add all the numbers together, and all the variables
3x+30=0
We move all terms containing x to the left, all other terms to the right
3x=-30
x=-30/3
x=-10

See similar equations:

| -3n+6=-4n-2 | | (3x-1)+4x+2=81 | | 2x+3+4x-12=15 | | 6x-2x+8=x-5+13 | | 3+2(x-5)=-5x | | -6(7+6v)=48 | | 2(u-2)=-6u+12 | | 41^2a-17=4a-11 | | 1/4(d-1)=3 | | -8=4(u+10) | | 4(2x–3)=3+8x–11 | | 14+7.6n=8+7.9n | | 7x−4=10x+14 | | (6s+12.5=105) | | -5(v-4)-5=-3(v-1) | | -36=3(w-6)-5w | | -5x-3=-9 | | −17c=21 | | 8(y+4)-2(y-1)=10-3(y-20) | | –6(2r+8)+7r+1=–10(r–3)–3(8–r) | | 7=−3x−2−6x | | 3(x-2)-5(2x+)=3 | | 3(2x−5)−4x+8=−2x+13(2x−5)−4x+8=−2x+13(2x−5)−4x+8=−2x+13(2x−5)−4x+8=−2x+13(2x−5)−4x+8=−2x+13(2x−5)−4x+8=−2x+13(2x−5)−4x+8=−2x+1 | | 3x-4-3=11 | | 18-b=-5b+7b | | 3(2x−5)−4x+8=−2x+1 | | 3(v+5)+3v=-3 | | 10+2x=2-12(x+1) | | 16.6=16.6=  x+15.8x+15.8 | | 2x-20-5x=x+5+x | | 2(6x-4)=3(6x+2 | | 7a+7a+(a+15)=180 |

Equations solver categories